When others are our real travels. Tribute to Lucio Gera as founding figure of the Interdisciplinary Seminar Permanent Literature, Aesthetics and Theology. In memoriam - Avenatti de Palumbo, Cecilia Inés (TEOLITERARIA - Revista de Literaturas e Teologias, 2013)
The objective of this report is to witness the inspiring role played Lucio Gera in the gestation of the Interdisciplinary Permanent Seminar Literature, Aesthetics and Theology. Towards the end of 1997 we convened to organize, within the framework of Theological Research Institute, Faculty of Theology (UCA), which was its first director, a seminar in which theology began to establish a dialogue with the academic literature. The multifaceted figure of Lucio Gera, guide and mentor of several generations, was also deployed in the search field of beauty. Reducing overcomes dualisms, from the look recapitulation of death, his figure is exaggerated in fertility lavished love and invites us to continue to open new paths. Keywords: Lucio Gera, literature and theology, interdisciplinarity